1994
DOI: 10.1116/1.578909
|View full text |Cite
|
Sign up to set email alerts
|

Structural and morphological characterization of Nb2O5 thin films deposited by reactive sputtering

Abstract: Amorphous Nb2O5 thin films of three different thicknesses (10, 100, 400 nm) were deposited onto SiO2/Si substrates by reactive sputtering in an Ar–O2 plasma. Thermal treatments were performed at different temperatures between 500 and 1100 °C. The structural and morphological evolution with temperature is shown to be dependent on the film thickness. At 600 °C, the films essentially crystallize in the TT phase. On the thickest films, the T phase also appears. Annealing at higher temperature progressively increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…It is difficult to identify these two phases [28]. It is claimed that all refractions of TT phase correspond to one or a pair of closely spaced peaks of the T phase [13]. Thus, the TT phase is believed to be a poorly crystallized state of the T phase because of their very similar crystal structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to identify these two phases [28]. It is claimed that all refractions of TT phase correspond to one or a pair of closely spaced peaks of the T phase [13]. Thus, the TT phase is believed to be a poorly crystallized state of the T phase because of their very similar crystal structures.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous phases such as TT-, T-, B-, M-, H-, N-, P-and R-Nb 2 O 5 have been reported [11][12]. A pseudo hexagonal structure (TT phase) is observed at lower temperatures and it changes to orthorhombic structure (T phase) by being heated continuously [13]. It has been reported that orthorhombic "low-temperature" T-Nb 2 O 5 phase, in which niobium atoms are mainly surrounded by seven or six oxygen atoms forming pentagonal bipyramids or distorted octahedrons while the few remaining niobium atoms are coordinated to nine oxygen atoms in interstitial sites, is formed between 500 -800 °C [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Niobium oxides find a variety of applications in modern technology in different components ranging from capacitors [1], to waveguides [2], oxygen sensors [3] and as corrosion resistant material [4]. Apart from this, niobium oxide films are used as high refractive index layers in optical interference filters [5] which consist of a multilayer stack of high and low refractive index materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used in various fields such as optical waveguides [2], modulators [3], capacitors [4], oxygen sensors [5], catalysts [6], as a negative electrode in rechargeable batteries using V 2 O 5 and Li 2 MnO 4 as positive electode [7,8] etc. Nanocrystalline dye sensitized solar cell solar cells (DSSC, Graetzel cell) using Nb 2 O 5 thin film have been reported by Aegerter [9].…”
Section: Introductionmentioning
confidence: 99%